Design of a Website-Based New Student Registration Information System Using the Waterfall Method at RA Al Khoeriyah Banyuresmi Garut - Sidiq, Purnomo (RISTEC : Research in Information Systems and Technology, 2024)
This research is a result that describes the design of a website-based new student registration information system to improve the current system. The reason on the resultsservations and interviews conducted with sources where providing information regarding the placement of intemship students is still done manually because there are no media or facilities that schools can use to provide registration information to prospective students. Therefore, we need a media that can present information on new student registration at RA Al Khoeriyah. The method used in designing this application is using the waterfall method to make the process of providing information more effective. Then this new student registration website was created by making a design using UML modeling. Before it was developed into a complete application by the developer the design was in the form of a waterfall, first by the validator using a validation sheet and the results obtained in the validation sheet stated that the category obtained in the validation sheet states that the categories obtained are good and very good. So it can be stated that the design of this website-based new student registration information system is worthy of being a reference for further system.